27. Results of cement-augmented pedicle screw surgery in the treatment of thoracic and lumbar spine collapse in severe osteoporosis patients - Nha, Le Hoang; Hung, Kieu Dinh; Thuong, Do Cong; Nhat, Nguyen Huu (Tạp chí Nghiên cứu Y học, 2024)
Objective: This 2023 study aimed to assess pain relief, functional recovery, and kyphosis correction following pedicle screw surgery with cement augmentation in severe osteoporosis patients with vertebral collapse. Methods: Seventy-one patients underwent surgery and were evaluated for postoperative pain reduction (VAS score), functional improvement (ODI score), vertebral kyphosis angle, pre- and postoperative spinal curvature angles, and complications. Results: The study included 71 participants (13 males, 58 females; mean age 67.6±6.7 years). Trauma sources included falls (47.9%), heavy lifting (17%), and unclear mechanisms (35.2%). Mean hospital stay was 12±6.5 days. Preoperative, postoperative, and 1/6-month VAS scores were 8.7, 2.2, 1.5, 0.9 respectively (p<0.001). ODI scores were 77.6, 52.8, 43.0, 37.9 respectively (p<0.001). Kyphotic angle (vertebral body) decreased from preop 12.9° to postop 9.9°, 1/6 months 10.1° (p<0.001); at surgical site, preop 15.4° to 1/6 months 11.9° (p<0.001). Cement leakage occurred in 36.6% of cases, mostly asymptomatic, with distribution in the disc space (2.8%), blood vessels (8.5%), around vertebral body (12.7%), spinal canal (14.1%), and lungs (2.8%). Conclusion: Pedicle screw fixation with enhanced cement augmentation effectively manages severe osteoporotic vertebral compression fractures, providing significant pain relief, improved postoperative function, and spinal alignment. Symptomatic cement leakage is rare.